2019
DOI: 10.1021/acs.jpcb.8b11994
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Nanoparticles Prepared Using Redox-Active Transition Metals

Abstract: Autoxidation of dopamine to polydopamine by dissolved oxygen is a slow process that requires highly alkaline conditions. Polydopamine can be formed rapidly also in mildly acidic and neutral solutions by using redox-active transition-metal ions. We present a comparative study of polydopamine nanoparticles formed by autoxidation and aerobic or anaerobic oxidation in the presence of Ce(IV), Fe(III), Cu(II), and Mn(VII). The UV–vis spectra of the purified nanoparticles are similar, and dopaminechrome is an early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 93 publications
0
33
0
1
Order By: Relevance
“…To elucidate the difference in performance between the two phase transfer processes, a series of surface characterizations (TGA, FTIR, neutron scattering, and XPS) were performed. TGA can quantify the extent of the phase transfer since it is known that hydrophilic films can be deposited around colloidal NPs for certain phase transfer agents, such as polydopamine [29] . The TGA results are shown in Table 2 and Figure S6 for the as‐synthesized and phase transferred samples.…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the difference in performance between the two phase transfer processes, a series of surface characterizations (TGA, FTIR, neutron scattering, and XPS) were performed. TGA can quantify the extent of the phase transfer since it is known that hydrophilic films can be deposited around colloidal NPs for certain phase transfer agents, such as polydopamine [29] . The TGA results are shown in Table 2 and Figure S6 for the as‐synthesized and phase transferred samples.…”
Section: Resultsmentioning
confidence: 99%
“…Adding boric acid to dopamine solutions after a given oxidation and self-assembly duration allows to stop the growth of the PDA based nanoparticles to a controlled and reproducible size provided the boric acid/dopamine ratio is higher than 5 [47]. A recent study showed that a vast repertoire of oxidants can be used to rapidly prepare polydopamine under aerobic or anaerobic conditions, also in mildly acidic aqueous solutions, and at room temperature [48]. Also, the use of strong oxidants such as sodium periodate leads to PDA formation in a much shorter time [49].…”
Section: How To Avoid Precipitation In Solution and To Produce Stablementioning
confidence: 99%
“…As a prominent example, Mun et al reported that, by using the atmospheric pressure plasma and DA mist, a ≈536 nm thick polymer film could be deposited in 60 s. [29] The inclusion of unique reagents is also a valuable approach to regulate the polymerization of DA, aimed at altered deposition dynamics and tailored structures and properties of PDA. [25,[106][107][108][109][110][111] On the one hand, many oxidants, such as Cu 2+…”
Section: Special Conditions For Catechol Polymerizationmentioning
confidence: 99%
“…It was reported that the formal potential of the Cu 2+ / Cu + could be positively shifted to +0.53 V in the presence of 0.1 m Cl − . [108,184] Likewise, reactive oxygen species generated from UV irradiation can accelerate PDA deposition (curve 6). [27,100] Du et al investigated the polymerization of DA under pH 7.0 and 8.5, with/without UV irradiation.…”
Section: Control Of Pda Coating Kineticsmentioning
confidence: 99%
See 1 more Smart Citation